Latest development in the synthesis of ursodeoxycholic acid (UDCA): a critical review - Tonin, Fabio; Arends, Isabel W. C. E. (Beilstein Journal of Organic Chemistry, 2018)
Ursodeoxycholic acid (UDCA) is a pharmaceutical ingredient widely used in clinics. As bile acid it solubilizes cholesterol gallstones and improves the liver function in case of cholestatic diseases. UDCA can be obtained from cholic acid (CA), which is the most abundant and least expensive bile acid available. The now available chemical routes for the obtainment of UDCA yield about 30% of final product. For these syntheses several protection and deprotection steps requiring toxic and dangerous reagents have to be performed, leading to the production of a series of waste products. In many cases the cholic acid itself first needs to be prepared from its taurinated and glycilated derivatives in the bile, thus adding to the complexity and multitude of steps involved of the synthetic process. For these reasons, several studies have been performed towards the development of microbial transformations or chemoenzymatic procedures for the synthesis of UDCA starting from CA or chenodeoxycholic acid (CDCA). This promising approach led several research groups to focus their attention on the development of biotransformations with non-pathogenic, easy-to-manage microorganisms, and their enzymes. In particular, the enzymatic reactions involved are selective hydrolysis, epimerization of the hydroxy functions (by oxidation and subsequent reduction) and the specific hydroxylation and dehydroxylation of suitable positions in the steroid rings. In this minireview, we critically analyze the state of the art of the production of UDCA by several chemical, chemoenzymatic and enzymatic routes reported, highlighting the bottlenecks of each production step. Particular attention is placed on the precursors availability as well as the substrate loading in the process. Potential new routes and recent developments are discussed, in particular on the employment of flow-reactors. The latter technology allows to develop processes with shorter reaction times and lower costs for the chemical and enzymatic reactions involved.
Keywords: bile acids; biotransformation; hydroxysteroid dehydrogenases; production process; UDCA

(untitled) - Ikegami, T.; Matsuzaki, Y. (Hepatol. Res., 2008)

(untitled) - Crosignani, A.; Battezzati, P. M.; Setchell, K. D. R.; Invernizzi, P.; Covini, G.; Zuin, M.; Podda, M. (Dig. Dis. Sci., 1996)

(untitled) - Salen, G.; Colalillo, A.; Verga, D.; Bagan, E.; Tint, G.; Shefer, S. (Gastroenterology, 1980)

(untitled) - Colombo, C.; Setchell, K. D. R.; Podda, M.; Crosignani, A.; Roda, A.; Curcio, L.; Ronchi, M.; Giunta, A. (J. Pediatr., 1990)

(untitled) - Colombo, C.; Crosignani, A.; Assaisso, M.; Battezzati, P. M.; Podda, M.; Giunta, A.; Zimmer-Nechemias, L.; Setchell, K. D. R. (Hepatology (Hoboken, NJ, U. S.), 1992)

(untitled) - Colombo, C.; Battezzati, P. M.; Podda, M.; Bettinardi, N.; Giunta, A. (Hepatology (Hoboken, NJ, U. S.), 1996)

(untitled) - Combes, B.; Carithers, R. L.; Maddrey, W. C.; Lin, D.; McDonald, M. F.; Wheeler, D. E.; Eigenbrodt, E. H.; Muñoz, S. J.; Rubin, R.; Garcia-Tsao, G.; Bonner, G. F.; West, A. B.; et al. (Hepatology (Hoboken, NJ, U. S.), 1995)

(untitled) - Podda, M.; Zuin, M.; Battezzati, P. M.; Ghezzi, C.; De Fazio, C.; Dioguardi, M. L. (Gastroenterology, 1989)

(untitled) - Thistle, J. L. (Semin. Liver Dis., 1983)

(untitled) - Ward, A.; Brogden, R. N.; Heel, R. C.; Speight, T. M.; Avery, G. S. (Drugs, 1984)

(untitled) - Roda, E.; Bazzoli, F.; Labate, A. M. M.; Mazzella, G.; Roda, A.; Sama, C.; Festi, D.; Aldini, R.; Taroni, F.; Barbara, L. (Hepatology (Hoboken, NJ, U. S.), 1982)

(untitled) - Carrea, G.; Pilotti, A.; Riva, S.; Canzi, E.; Ferrari, A. (Biotechnol. Lett., 1992)

(untitled) - Hofmann, A. F. (Acta Chem. Scand., 1963)

(untitled) - Kanazawa, T.; Shimazaki, A.; Sato, T.; Hoshino, T. (Nippon Kagaku Zasshi, 1955)

(untitled) - Fieser, L. F.; Rajagopalan, S. (J. Am. Chem. Soc., 1950)

(untitled) - Sutherland, J. D.; Macdonald, I. A.; Forrest, T. P. (Prep. Biochem., 1982)

(untitled) - Prabha, V.; Ohri, M. (World J. Microbiol. Biotechnol., 2006)

(untitled) - Midtvedt, T.; Norman, A. (Acta Pathol. Microbiol. Scand., 1967)

(untitled) - Mahato, S. B.; Garai, S. (Steroids, 1997)

(untitled) - Eggert, T.; Bakonyi, D.; Hummel, W. (J. Biotechnol., 2014)

(untitled) - Bortolini, O.; Medici, A.; Poli, S. (Steroids, 1997)

(untitled) - Mukhopadhyay, S.; Maitra, U. (Curr. Sci., 2004)

(untitled) - Hofmann, A. F. (Arch. Intern. Med., 1999)

(untitled) - Fini, A.; Roda, A. (J. Lipid Res., 1987)

(untitled) - Bonar-Law, R. P.; Davis, A. P. (Tetrahedron, 1993)

Biotrasformazioni di Acidi Biliari - Maldonado Rodríguez, M. E. (2013)

(untitled) - Ahrens, E. H.; Craig, L. C. (J. Biol. Chem., 1952)

(untitled) - Carey, M. C. (Hepatology (Hoboken, NJ, U. S.), 1984)

(untitled) - Fossati, E.; Polentini, F.; Carrea, G.; Riva, S. (Biotechnol. Bioeng., 2006)

(untitled) - Washizu, T.; Tomoda, I.; Kaneko, J. J. (J. Vet. Med. Sci., 1991)

(untitled) - Iser, J. H.; Sali, A. (Drugs, 1981)

(untitled) - Carey, M. C. (N. Engl. J. Med., 1975)

(untitled) - Pedrini, P.; Andreotti, E.; Guerrini, A.; Dean, M.; Fantin, G.; Giovannini, P. P. (Steroids, 2006)

(untitled) - Christiaens, H.; Leer, R.; Pouwels, P.; Verstraete, W. (Appl. Environ. Microbiol., 1992)

(untitled) - Nakagawa, Y.; Hasegawa, A.; Hiratake, J.; Sakata, K. (Protein Eng., Des. Sel., 2007)

(untitled) - Torres-Gavilán, A.; Castillo, E.; López-Munguía, A. (J. Mol. Catal. B: Enzym., 2006)

(untitled) - Feng, Y.; Siu, K.; Wang, N.; Ng, K.-M.; Tsao, S.-W.; Nagamatsu, T.; Tong, Y. (J. Ethnobiol. Ethnomed., 2009)

(untitled) - Delgado, H.; Cedeño, C.; de Oca, N.; Villoch, A. (Rev. Salud Anim., 2015)

(untitled) - Delgado, D.; Roque, P.; Cedeño, P.; Villoch, C. (Rev. Salud Anim., 2015)

(untitled) - Delgado, H.; Cedeño, C.; Villoch, A.; Dueñas, R. (Rev. Salud Anim., 2015)

(untitled) - Volkman, J. (Appl. Microbiol. Biotechnol., 2003)

(untitled) - Huang-Minlon, B. Y. (J. Am. Chem. Soc., 1949)

(untitled) - Cranwell, P. B.; Russell, A. T.; Smith, C. D. (Synlett, 2016)

(untitled) - Newman, S. G.; Gu, L.; Lesniak, C.; Victor, G.; Meschke, F.; Abahmane, L.; Jensen, K. F. (Green Chem., 2014)

(untitled) - Parquet, E.; Lin, Q. (J. Chem. Educ., 1997)

(untitled) - Dietl, A.; Ferousi, C.; Maalcke, W. J.; Menzel, A.; de Vries, S.; Keltjens, J. T.; Jetten, M. S. M.; Kartal, B.; Barends, T. R. M. (Nature, 2015)

(untitled) - Sato, Y.; Ikekawa, N. (J. Org. Chem., 1959)

(untitled) - Harris, J. N.; Hylemon, P. B. (Biochim. Biophys. Acta, Lipids Lipid Metab., 1978)

(untitled) - Braun, M.; Lünsdorf, H.; Bückmann, A. F. (Eur. J. Biochem., 1991)

(untitled) - Macdonald, I. A.; Jellett, J. F.; Mahony, D. E.; Holdeman, L. V. (Appl. Environ. Microbiol., 1979)

(untitled) - Macdonald, I. A.; Meier, E. C.; Mahony, D. E.; Costain, G. A. (Biochim. Biophys. Acta, Lipids Lipid Metab., 1976)

US Patent - Aigner, A.; Gross, R.; Schmid, R. D.; Braun, M.; Mauer, S. (Novel 12 alpha-hydroxysteroid dehydrogenase, production and use thereof, 2011)

Eur. Patent - Fossati, E.; Carrea, G.; Riva, S.; Polentini, F. (Process for the selective oxydation of cholic acid, 2006)

(untitled) - Edenharder, R. (J. Steroid Biochem., 1984)

U.S. Patent - Saltzman, W. H. (Synthesis of steroids, 1976)

(untitled) - Wells, J. E.; Hylemon, P. B. (Appl. Environ. Microbiol., 2000)

(untitled) - Ridlon, J. M.; Kang, D.-J.; Hylemon, P. B. (Anaerobe, 2010)

(untitled) - Ridlon, J. M.; Harris, S. C.; Bhowmik, S.; Kang, D.-J.; Hylemon, P. B. (Gut Microbes, 2016)

WO Patent - Ferrari, M.; Zinetti, F. (Process for preparing high purity ursodeoxycholic acid)

(untitled) - Dangate, P. S.; Salunke, C. L.; Akamanchi, K. G. (Steroids, 2011)

(untitled) - Parr, R. G.; Yang, W. (J. Am. Chem. Soc., 1984)

(untitled) - Samuelsson, B. (Acta Chem. Scand., 1960)

(untitled) - Coleman, J. P.; Hudson, L. L.; Adams, M. J. (J. Bacteriol., 1994)

(untitled) - Baron, S. F.; Franklund, C. V.; Hylemon, P. B. (J. Bacteriol., 1991)

(untitled) - Ferrandi, E. E.; Bertolesi, G. M.; Polentini, F.; Negri, A.; Riva, S.; Monti, D. (Appl. Microbiol. Biotechnol., 2012)

(untitled) - Bakonyi, D.; Hummel, W. (Enzyme Microb. Technol., 2017)

(untitled) - Yoshimoto, T.; Higashi, H.; Kanatani, A.; Lin, X. S.; Nagai, H.; Oyama, H.; Kurazono, K.; Tsuru, D. (J. Bacteriol., 1991)

(untitled) - Ueda, S.; Oda, M.; Imamura, S. (Int. J. Biol. Macromol., 2004)

(untitled) - Bennett, M. J.; McKnight, S. L.; Coleman, J. P. (Curr. Microbiol., 2003)

(untitled) - Ji, W.; Chen, Y.; Zhang, H.; Zhang, X.; Li, Z.; Yu, Y. (Microbiol. Res., 2014)

WO Patent - Monti, D.; Ferrandi, E. E.; Riva, S.; Polentini, F. (New process for the selective oxidation of bile acids, their salts or derivatives, 2012)

U.S. Patent - Gupta, A.; Tschentscher, A.; Bobkova, M. (Process for the enantioselective reduction and oxidation, respectively, of steroids, 2009)

(untitled) - O'Leary, N. A.; Wright, M. W.; Brister, J. R.; Ciufo, S.; Haddad, D.; McVeigh, R.; Rajput, B.; Robbertse, B.; Smith-White, B.; Astashyn, D. A.-A. A.; Batretdin, A.; Bao, Y.; et al. (Nucleic Acids Res., 2015)

(untitled) - Liu, L.; Aigner, A.; Schmid, R. D. (Appl. Microbiol. Biotechnol., 2011)

(untitled) - Lee, J.-Y.; Arai, H.; Nakamura, Y.; Fukiya, S.; Wada, M.; Yokota, A. (J. Lipid Res., 2013)

(untitled) - Zheng, M.-M.; Chen, K.-C.; Wang, R.-F.; Li, H.; Li, C.-X.; Xu, J.-H. (J. Agric. Food Chem., 2017)

WO Patent - Hummel, W.; Bakonyi, D. (7-beta-hydroxysteroid dehydrogenase mutants and process for the preparation of ursodeoxycholic acid, 2016)
; .

(untitled) - Bovara, R.; Carrea, G.; Riva, S.; Secundo, F. (Biotechnol. Lett., 1996)

(untitled) - Monti, D.; Ottolina, G.; Carrea, G.; Riva, S. (Chem. Rev., 2011)

(untitled) - Macdonald, I. A.; Hutchison, D. M. (J. Steroid Biochem., 1982)

(untitled) - Sutherland, J. D.; Macdonald, I. A. (J. Lipid Res., 1982)

(untitled) - Macdonald, I.; Rochon, Y.; Hutchison, D.; Holdeman, L. (Appl. Environ. Microbiol., 1982)

(untitled) - Hirano, S.; Masuda, N. (J. Lipid Res., 1982)

(untitled) - Sutherland, J. D.; Holdeman, L. V.; Williams, C. N.; Macdonald, I. A. (J. Lipid Res., 1984)

(untitled) - Medici, A.; Pedrini, P.; Bianchini, E.; Fantin, G.; Guerrini, A.; Natalini, B.; Pellicciari, R. (Steroids, 2002)

(untitled) - Braun, M.; Sun, B.; Anselment, B.; Weuster-Botz, D. (Appl. Microbiol. Biotechnol., 2012)

(untitled) - Sun, B.; Kantzow, C.; Bresch, S.; Castiglione, K.; Weuster-Botz, D. (Biotechnol. Bioeng., 2013)

(untitled) - Bakonyi, D.; Wirtz, A.; Hummel, W. (Z. Naturforsch., B: Chem. Sci., 2012)

(untitled) - Liu, L.; Braun, M.; Gebhardt, G.; Weuster-Botz, D.; Gross, R.; Schmid, R. D. (Appl. Microbiol. Biotechnol., 2013)

(untitled) - Giovannini, P. P.; Grandini, A.; Perrone, D.; Pedrini, P.; Fantin, G.; Fogagnolo, M. (Steroids, 2008)

(untitled) - Monti, D.; Ferrandi, E. E.; Zanellato, I.; Hua, L.; Polentini, F.; Carrea, G.; Riva, S. (Adv. Synth. Catal., 2009)

(untitled) - Zheng, M.-M.; Wang, R.-F.; Li, C.-X.; Xu, J.-H. (Process Biochem. (Oxford, U. K.), 2015)

(untitled) - Zheng, M.-M.; Chen, F.-F.; Li, H.; Li, C.-X.; Xu, J.-H. (ChemBioChem, 2017)

(untitled) - Ji, Q.; Tan, J.; Zhu, L.; Lou, D.; Wang, B. (Biochem. Eng. J., 2016)

(untitled) - Sawada, H.; Kulprecha, S.; Nilubol, N.; Yoshida, T.; Kinoshita, S.; Taguchi, H. (Appl. Environ. Microbiol., 1982)

(untitled) - Carlström, K.; Kirk, D.; Sjövall, J. (J. Lipid Res., 1981)

(untitled) - Kollerov, V. V.; Monti, D.; Deshcherevskaya, N. O.; Lobastova, T. G.; Ferrandi, E. E.; Larovere, A.; Gulevskaya, S. A.; Riva, S.; Donova, M. V. (Steroids, 2013)

(untitled) - Kollerov, V. V.; Lobastova, T. G.; Monti, D.; Deshcherevskaya, N. O.; Ferrandi, E. E.; Fronza, G.; Riva, S.; Donova, M. V. (Steroids, 2016)

(untitled) - Möbus, E.; Maser, E. (J. Biol. Chem., 1998)

(untitled) - Arends, I. W. C. E.; Li, Y.-X.; Ausan, R. A.; Sheldon, R. A. (Tetrahedron, 2006)

(untitled) - Igimi, H.; Carey, M. C. (J. Lipid Res., 1980)

Physical chemistry of bile, Compr. Physiol. - Cabral, D. J. (John Wiley & Sons, 2010)

(untitled) - Carey, M. C.; Small, D. M. (Arch. Intern. Med., 1972)

(untitled) - Hisadome, T.; Nakama, T.; Itoh, H.; Furusawa, T. J. (Gastroenterol. Jpn., 1980)

(untitled) - Khmelnitsky, Y. L.; Levashov, A. V.; Klyachko, N. L.; Martinek, K. (Enzyme Microb. Technol., 1988)

(untitled) - Riva, S.; Bovara, R.; Zetta, L.; Pasta, P.; Ottolina, G.; Carrea, G. (J. Org. Chem., 1988)

(untitled) - Bovara, R.; Canzi, E.; Carrea, G.; Pilotti, A.; Riva, S. (J. Org. Chem., 1993)

WO Patent - Monti, D.; Ferrandi, E. E.; Riva, S.; Polentini, F. (Process for the selective reduction of bile acids, their salts or derivatives, in a biphasic system, 2013)

(untitled) - Ricca, E.; Brucher, B.; Schrittwieser, J. H. (Adv. Synth. Catal., 2011)

(untitled) - Oroz-Guinea, I.; García-Junceda, E. (Curr. Opin. Chem. Biol., 2013)

Cascade Biocatalysis Integrating Stereoselective and Environmentally Friendly Reactions - Riva, S.; Fessner, W.-D. (John Wiley & Sons, 2014)